Éléments de compréhension du processus de politisation du discours sur la gestion intégrée des zones côtières - Céline Ségalini (Développement Durable et Territoires)
Nowadays, the discourse on “integrated coastal zone management” (ICZM) is essential in coastal management policies. Through a comprehension of the evolution of the environmental discourse since the 1970s, this paper offers a fresh perspective to understand the politicization of the ICZM approach. After showing what mechanisms are generally put forward in the literature to depict this politicization, it emphasizes the importance considering its overall cognitive framework. Thus, politicization of ICZM discourse is partly linked with the social recognition of sustainable development thought, which breaks with the dominant critical environmentalism of the 1970s.